Consumo de bebidas açucaradas e associação com riscos cardiovasculares em adolescentes - Neves, Ana Flávia Gomes de Britto (2019)
The consumption of sugary drinks grew in parallel with the Chronic Non-Communicable Diseases index. Adolescence is a period in which great human potential is developed and cardiovascular risks that affect this phase are responsible for serious epidemiological consequences. Unhealthy eating habits, such as the consumption of sugary drinks, are common among adolescents and have an impact on the health of individuals in the short and long term. OBJECTIVE: To describe the consumption of sugary drinks and their association with cardiovascular risk factors in Brazilian adolescents. METHODS: The research used the database of the Study of Cardiovascular Risks in Adolescents (ERICA), a Brazilian schoolbased survey. The sample consisted of 36,956 adolescents aged 12 to 17 years, of both sexes, selected by probabilistic sampling. Sociodemographic variables were collected through a selfadministered questionnaire, nutritional status and blood pressure by physical examination and glycemic and lipid profile through fasting blood test. Food consumption was investigated using a 24-hour recall (R24h). Six food groups were categorized and considered as cardiovascular risks, overweight, hypertension, hyperglycemia and dyslipidemia. Prevalences, means and medians were estimated. A 95% confidence interval and a 5% significance level were applied. The χ2 and t-Student tests were used to compare variables analyzed descriptively. Inferential associations between exposure and outcome were performed using the Regression Model and the Mantel-Haenszel Method. Sociodemographic and behavioral factors were treated as adjustment variables. The survey module of the Stata® version 14.0 program was used to analyze complex sample data. RESULTS: There was a predominance of females (60%) and the average age was 14.7 years, being higher among girls. The average number of calories consumed daily by Brazilian adolescents was 2,297.12 kcal. The presence of sugary drinks is common in the diet of these adolescents. Juices / soft drinks and soft drinks were the most mentioned drinks in R24h, respectively. They are relevant caloric sources in the diet of Brazilian adolescents and when stratified by sex and age, consumption habits can change between groups. The average energy and free sugar from sugary drinks, measured in calories, varied between groups, as did the amount in ml. The soft drinks had the largest daily portions, in milliliters, and the largest amount of calories from free sugar. The presence of cardiovascular risks reflected in the average amount (ml) of sugary drinks consumed by adolescents and the size of the daily portion (≥450ml) of normal and diet sodas was positively associated with weight gain and elevated arterial pressure levels. CONCLUSION: Sugary drinks were frequently mentioned at R24h. The presence of cardiovascular risks in adolescents can influence the average amount (ml) of daily consumption of these drinks. Significant associations between portion size of soft drinks, overweight and hypertension were identified. The consumption of sugary drinks should be considered in adolescence. Better understanding of the relationship between consumption of sugary drinks and cardiovascular risks in adolescence is essential for strengthening Public Health.